GE_GERICHTE P/10889/2012 vom 9. September 2014 - GE Cour de justice (2014)
ADMINISTRATION DES PREUVES; IN DUBIO PRO REO; RECEL; ACQUITTEMENT; INDEMNITÉ(EN GÉNÉRAL) | CP.160.1.1; CPP.389; CPP.10.3; CPP.429.1.A